Implementasi Kebijakan Tentang Pedoman Standar Pelayanan Pengguna Jasa di Bandar Udara Oesman Sadik Labuha - Salama, Safrin US (Journal of Public Administration and Local Governance, 2023)
The implementation of service standards has become a strategic issue to be discussed, especially in relation to its quality of service. Therefore, the purpose of this research is to analyze the implementation of service standards guidelines for service users at Oesman Sadik Labuha Airport. Descriptive analysis was chosen as the approach with qualitative research method. The unit of analysis is the manager of Oesman Sadik Labuha Airport. Data collection techniques were conducted through observation, interviews, and document study. The researcher made an interview guideline as a guide in conducting interviews with informants at the research location. The data analysis stage begins with data processing and preparation, reading data, coding data, displaying themes in narrative form, and data interpretation. The results of this study explain that the manager of Oesman Sadik Labuha Airport has implemented service standards for airport service users in accordance with Minister of Transportation Regulation Number 178 of 2015, but there are still some facilities that are not available such as departure and arrival immigration services, customs services, facilities for special needs users, and seven other facilities. Communication, resource, disposition, and bureaucratic structure factors that have a positive and negative influence on its implementation.